Defect and Material Mechanics Proceedings of the International Symposium on Defect and Material Mechanics (ISDMM), held in Aussois, France, March 25–29, 2007 - Dascalu, C.; Dascalu, C.; Maugin, Gérard A.; Maugin, Gérard A.; Stolz, Claude.; Stolz, Claude. (Springer Netherlands : Imprint: Springer, 2008)
This volume presents recent developments in the theory of defects and the mechanics of material forces. Most of the contributions were presented at the International Symposium on Defect and Material Forces (ISDMM2007), held in Aussois, France, March 25-29, 2007. The mechanics of material forces, originated in the works of Eshelby, provide a rational framework for the description of driving forces on evolving inhomogeneities and structural changes in continua. The general eshelbian mechanics formulation comes up with a unifying treatment of different phenomena like fracture and damage evolution, phase transitions, plasticity and dislocation motion, etc. The articles concern both theoretical and computational aspects of the material mechanics of defects. Among the addressed topics are fracture and damage, electromagnetoelasticity, plasticity, distributed dislocations, thermodynamics, poroelasticity, generalized continua, structural optimization, conservation laws and symmetries, multiscale approaches, and numerical solution strategies. This is a hardbound spin-off reprinted from The International Journal of Fracture 147:1-4.